On Sea Level Rise - Van der Meulen, Geert; Leung, Ranee; Storms, Joep; Sanaan Bensi, Negar; Bacchin, Taneha K.; Timmermans, Jos; Hooimeijer, Fransje; Van Boxtel, Elma; Koreman, Kristian (Journal of Delta Urbanism, 2020)
While the severity of the climate crisis calls for a discussion on transformative and potentially disruptive change, science, engineering, design, governance and practice are currently too detached to effectively contribute to such discussions. The spatial manifestation of climate crisis rarely appeals to one’s imagination. Yet, when reviewing the range of sea level rise projections and their accelerated rate of change, it is clear that understanding when and why to navigate between mitigation, adaptation and transformation measures is essential for flourishing coastal communities globally. The Netherlands is one of those and has been characterised by a long history of renowned flood risk and water management as well as spatial planning. Facing the potential extreme scenarios of sea level rise, the country now however struggles to include measures preparing for a shift from incremental to the required transformative strategies. This research project identifies the criticalities by means of a risk matrix and stress maps as an initial act to introduce the Sea Level Impact Knowledge Collect and its transdisciplinary Research by Design approach to guide the discussion on transformative change and its implementation in living labs.